Secondary Oral Anti-hyperglycemic Drugs Failure in Type 2 Diabetes Patients Infected with Hepatitis C Virus - Aye, Than; Aye, Htar; Oo, Ei (Journal of Diabetes and Endocrine Practice, 2020)
Background and Objective: Chronic hepatitis C infection can affect glycemic control in patients with diabetes mellitus (DM). This study was done to assess the influence of hepatitis C viral infection compared to hepatitis B viral infection and noninfected cases on the occurrence of secondary oral anti-hyperglycemic drugs (OADs) failure in type 2 diabetes mellitus (T2DM) patients. Patients and Methods: This prospective study was conducted on 1293 T2DM patients who had their hepatitis B and C status checked by the enzyme-linked immunosorbent assay method. Glycemic management was done according to the standard guidelines, and glycemic control was reviewed after 6 months of enrollment. Patients who had hemoglobin HbA1c >7.5% in spite of taking >75% of the maximum dosage of three OADs, that is, metformin, sulfonylurea, and thiazolidinediones were selected. Those who were already taking insulin therapy regardless of HbA1c were also considered as secondary OADs failure. The status of secondary OADs failure was analyzed in three groups: hepatitis C virus (HCV) positive, hepatitis B virus (HBV) positive, or noninfected patients. Results: Of selected 1293 cohorts, DM with HCV positive was 152 (11.7%), and DM with HBV positive was 111 (8.5%). Among 152 HCV-positive patients, secondary OADs failure was detected in 64 (42.1%), and in those with 111 HBV-positive patients, it was detected in 30 patients (27.02%), whereas it was 177 of 1030 noninfected patients (17.1%). Conclusion: Hepatitis C infection is more common than hepatitis B infection among diabetes patients. Secondary OADs failure is significantly associated with HCV-infected diabetes patients compared to other groups, and timely consideration of insulin initiation is important in these cases.
Keywords: Hepatitis C virus; insulin therapy; secondary oral anti-hyperglycemic drugs failure